2018
DOI: 10.46311/2318-0579.55.euj2464
|View full text |Cite
|
Sign up to set email alerts
|

Atividade Antibacteriana Do Extrato Etanólico Bruto Da Gossypium Hirsutum L. Contra Pseudomonas Aeruginosa

Abstract: A busca do conhecimento a cerca de plantas medicinais vem acompanhado a evolução do homem através dos tempos. A evolução das espécies bacterianas e resistência microbiana delas, vem crescendo preocupantemente. A Gossypium hirsutum L. é popularmente conhecida como algodoeiro e suas folhas tem sido usadas com diversos fins terapêuticos. O presente estudo objetiva avaliar in vitro a ação antibacteriana do extrato da G. hirsutum L. contra Pseudomonas aruginosa. Para a avaliação da atividade antibacteriana e determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Ethnobotanical studies have demonstrated that the species Gossypium hirsutum is traditionally used in the preparation of antiseptic remedies for a vaginal wash in the Chapada do Araripe region (Ceará, Brazil) [14]. Accordingly, evidence has indicated that this species presents antifungal activity [15][16][17], especially due to the presence of phenolic compounds such as flavonoids and terpenes [9,18,19]. However, the potential of this species to combat pathogenic Candida strains remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnobotanical studies have demonstrated that the species Gossypium hirsutum is traditionally used in the preparation of antiseptic remedies for a vaginal wash in the Chapada do Araripe region (Ceará, Brazil) [14]. Accordingly, evidence has indicated that this species presents antifungal activity [15][16][17], especially due to the presence of phenolic compounds such as flavonoids and terpenes [9,18,19]. However, the potential of this species to combat pathogenic Candida strains remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%